Radiological and clinical outcome of selective thoracic fusion for patients with Lenke 1C and 2C adolescent idiopathic scoliosis with a minimum follow-up of 2 years - Kwan, Mun Keong; Chiu, Chee Kidd; Tan, Pheng Hian; Chian, Xue Han; Ler, Xin Yi; Ng, Yun Hui; Ng, Sherwin Johan; Goh, Saw Huan; Chan, Chris Yin Wei (Elsevier, 2018)
Background Context: In Lenke 1C and 2C curves, the choice between selective thoracic fusion (STF) versus non-selective thoracic fusion as the optimal surgical treatment is controversial. Objective: This study aimed to assess the radiological and clinical outcome of patients with Lenke 1C and 2C curves treated with STF. Study Design: This is a retrospective study. Patient Sample: A total of 44 patients comprised the study sample. Methods: Forty-four patients with Lenke 1C and 2C curves with adolescent idiopathic scoliosis who underwent STF were reviewed. Radiological parameters and Scoliosis Research Society (SRS)-22r scores were assessed preoperatively, postoperatively, and on final follow-up. The incidence of coronal decompensation, lumbar decompensation, and adding-on phenomenon were reported. Results: Mean follow-up duration was 45.1±12.3 months and mean age was 17.0±5.1 years. The preoperative middle thoracic and thoracolumbar/lumbar (MT:TL/L) Cobb angle ratio was 1.4±0.3 and the MT:TL/L apical vertebra translation (AVT) ratio was 1.6±0.8. Final follow-up coronal balance was −13.0±11.5 mm, main thoracic AVT was 6.9±11.8 mm, and lumbar AVT was −20.4±13.8 mm (p<.05). Lumbar Cobb angle improved from 47.5°±7.8° to 24.9°±8.2° after operation and 23.3°±9.8° at final follow-up. The spontaneous lumbar curve correction rate was 50.9%. There were 9 patients (20.5%) who had coronal decompensation, 4 patients (9.1%) who had lumbar decompensation, and 11 patients (25.0%) who had adding-on phenomenon. We did not perform any revision surgery. The SRS-22r scores improved significantly in the overall scores, self-image, and mental health domain. Conclusions: Selective thoracic fusion led to improvement in the radiological and clinical outcome for patients with Lenke 1C and 2C. Although no patients required revision surgery, the rate of coronal decompensation, lumbar decompensation, and adding-on phenomenon are significant.